Probiotics: A potential immunotherapeutic approach for the treatment of schizophrenia - Sandeep Grover; Amol Patil; Anit Kaur; Gaurav Garg (Wolters Kluwer Medknow Publications, 2019)
Probiotics are in use for physiological boosting, health supplement, and for treatment since historical time. Recently, the to-and-fro pathways linking the gut with the brain, explaining the indirect communication via modulation of immune function and levels of various neurotransmitters, have been discovered, but how precisely these modulations alter the levels of neurotransmitters contributing to the cognitive and other symptom improvements in patients with schizophrenia remains a new arena of research for psychiatry and psychology professionals. The germ-free mice experiments have been the game changer in the mechanistic exploration. The antimicrobial usage alters the local gut flora and hence is associated with psychiatric side effects that strengthen the association further. The changes in the genetics of these bacteria with different types of diet and its correlation with neurotransmitters production capacity and the psyche of the individual are indeed an emerging field for schizophrenia research. Redressal of issues such as manufacturing, the shelf life of probiotics, and stability of probiotics in the gut milieu, in the presence of food, secretions, and exact volume needed for particular age group will help in refining the dose duration of probiotic therapy. Clinical trials are underway for evaluating safety and efficacy in schizophrenia. The gut microorganism transplant and pharmacovigilance of probiotics are important areas yet to be addressed accurately. This paper elucidates the pathways, clinical studies, availability of probiotics in the Indian market with their composition, regulatory issues in India about the probiotic use, and future of probiotic research in schizophrenia.